WORKLOAD ANALYSIS FOR DETERMINING THE NUMBER OF EMPLOYEES AT BANKING COMPANIES - Purnomo, Hari (GEMA, 2015)
At recent times, some companies have made some improvements in workforce planning, including in banking company. This study is aimed to determine the workload at the banking companies in Special Region of Yogyakarta. The result of the workload calculation was used to determine the number of employee. The method used to determining the workload was based on the Standard Time calculation (ST) using a stopwatch. Such calculations were conducted in each element on the activities of a cash deposit, bank clearing, cash withdrawal and withdrawal with cheque. The result of standard time in each activity showed 8.48 minutes/activity for the cash deposit, 2.79 minutes/activity for the bank clearing, 8.65 minutes/activity for cash withdrawal, 8.16 minutes/activity for the withdrawal by cheque and 1.04 for workload calculation indicated the abnormality of the workload. By contrast, the result of workload calculation was at the tolerance without any need to hire employee